Dampak Sosial Terhadap Anak Putus Sekolah (Studi Kasus SMA X Kecamatan Bandar Petalangan Kabupaten Pelalawan) - Nurmayana,; Akmal Latif, Syahrul (Sisi Lain Realita, 2024)
The purpose of this study was to determine the factors causing school dropouts in SMA X Bandar Petalangan Subdistrict, Pelalawan Regency and what are the social impacts that occur on school dropouts in SMA X Bandar Petalangan Subdistrict, Pelalawan Regency. In this study the author uses a qualitative method using descriptive data. This research was conducted at SMA X, Bandar Petalangan District, Pelalawan Regency. The key informants and informants of this study were victims of divorce, parents of victims, school principals, BK teachers and the community. Analysis of this research data using descriptive analysis. Results Based on research and discussion, the key is that the cause of dropping out of school in Bandar Petalangan District is generally due to economic factors. This is evident from the parents of children who have dropped out of school who only work as farmers with low incomes, so that the need for education is insufficient which ultimately causes children to drop out of school. Low parental education (graduated from elementary school/equivalent) results in parents being less important in educating their children. This is evidenced by the lack of parental supervision and understanding of the subject matter. Peers who also experience school dropouts also cause children to also drop out of school. This is evident from the informants of children who have dropped out of school also have peers who have dropped out of school